ANALISIS PENGARUH MOTIVASI KERJA, DISIPILIN KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA PT LOTTEMART WHOLESALE SEMARANG) - Alfianti, Nur Kasanah; Indriyatni, Lies (STIE PENA, 2024)
This study aims to find out whether Work Motivation, Work Discipline, and Work Environment affect Employee Performance. Sampling is carried out by the Purposive Sampling method, which is a sampling method with certain criteria. The results of this study show that Work Motivation has a positive and significant effect on Employee Performance, Work Discipline has a positive and significant effect on Employee Performance, and Work Environment has a positive and significant effect on Employee Performance. Work Motivation, Work Discipline, and Work Environment together or simultaneously have a significant effect on Employee Performance